Characteristics of regulations governing the ownership of potentially dangerous dog breeds in Latin American and Caribbean countries - Manco Santillán, Patricia Lucero del Pilar (2025)
The objective of this study was to evaluate and compare regulations governing potentially dangerous dog breeds in Latin America and the Caribbean, and to contrast them with the regulations in force in Peru. Information was gathered through a bibliographic review of laws, regulations, and provisions established by countries in the region regarding the ownership of potentially dangerous dog breeds. In this way, summary tables were used to compare the overlaps and discrepancies between the different components of the legislation. This study evaluated 16 regulations from 11 countries in Latin America and the Caribbean. Regarding canine characteristics, Peru focused more on breed, behavior, and training, and less on anatomical features and the potential to cause injury. On the other hand, it was determined that the American Pit Bull Terrier was the most frequently mentioned breed. It was also identified that in countries such as Peru, Argentina (Buenos Aires), Chile, Colombia, Costa Rica, Ecuador, Guatemala, and Uruguay, dog owners are financially responsible for injuries caused by their animals. Furthermore, violations may be expressed in terms of legal minimum wages, applicable tax units (UIT), or monetary value, and vary according to the severity of the injury and the applicable regulations in each country. Although the regulations share a common focus on responsible ownership of dogs considered potentially dangerous, there are differences that should be considered to make the Peruvian legislation more comprehensive.